Role and tasks of volunteers in the public health institution - Cambieri, Andrea; Catananti, Cesare; Candia, Luigi (Medicina e Morale, 1987)
In recent years, our country has undergone a radical transformation of its administrative structure in order to adapt to the new and no longer postponable demands for the decentralisation of state powers and competences